2015
DOI: 10.4269/ajtmh.14-0330
|View full text |Cite
|
Sign up to set email alerts
|

Insect-Specific Viruses Detected in Laboratory Mosquito Colonies and Their Potential Implications for Experiments Evaluating Arbovirus Vector Competence

Abstract: Abstract. Recently, there has been a dramatic increase in the detection and characterization of insect-specific viruses in field-collected mosquitoes. Evidence suggests that these viruses are ubiquitous in nature and that many are maintained by vertical transmission in mosquito populations. Some studies suggest that the presence of insect-specific viruses may inhibit replication of a super-infecting arbovirus, thus altering vector competence of the mosquito host. Accordingly, we screened our laboratory mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 45 publications
(68 reference statements)
1
60
0
Order By: Relevance
“…Indeed, given the very high prevalence of these viruses, it seems intuitively unlikely that these viruses are associated with severe disease in their hosts, and we propose that the most likely status for these viruses is either sublethal infection or commensal. This is supported by the observation that viruses have been detected in both laboratory mosquito colonies and insect cell lines that show little loss of fitness (29,30), although this clearly requires additional study.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, given the very high prevalence of these viruses, it seems intuitively unlikely that these viruses are associated with severe disease in their hosts, and we propose that the most likely status for these viruses is either sublethal infection or commensal. This is supported by the observation that viruses have been detected in both laboratory mosquito colonies and insect cell lines that show little loss of fitness (29,30), although this clearly requires additional study.…”
Section: Discussionsupporting
confidence: 54%
“…ISVs have been detected in both laboratory mosquito colonies (Bolling et al, 2015a) and insect cell lines in which they were initially discovered (Stollar and Thomas, 1975). One study found that colonies of mosquitoes from different geographic locations were infected with multiple ISVs, including Aedes flavivirus (AeFV) and CFAV (Bolling et al, 2015a).…”
Section: Impact Of Isvs On Experimental Studies-in Vitro and Lab Colomentioning
confidence: 99%
“…The available data suggest that ISFs are maintained in their mosquito hosts by vertical transmission and without causing deleterious effects. 9,38,39 In this regard, they behave like symbionts and constitute part of the insect's microbiome. Therefore, it seems likely that these symbiotic viruses may affect vector competence for arboviruses.…”
Section: Discussionmentioning
confidence: 99%
“…54 CFAV also have been isolated repeatedly from pools of male as well as female mosquitoes, 53,54 suggesting that the virus is maintained in nature by vertical transmission. Bolling and others 39 described a laboratory colony of Ae. albopictus, established from adults collected in Galveston, TX, that was persistently infected with CFAV; the virus was present in most of the mosquitoes of both sexes generation after generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation